Analisis Kinerja Keuangan Pemerintah Daerah Kabupaten Induk dan Kabupaten Pemekaran: Studi Kasus Kabupaten Sijunjung dan Kabupaten Dharmasraya - Halkadri Fitra; Febri Mukhlis; Sintia Rama Dani (Universitas Negeri Padang, 2020)
The purpose of this study was to determine the financial performance of the Sijunjung district and Dharmasraya districts. The study was conducted using quantitative data in the form of a budget realization report obtained from the Financial Examination Agency of West Sumatra Province. The method used is a quantitative descriptive method, to measure financial performance through financial ratios using 10 indicators. The results showed that: (1)Sijunjung and Dharmasraya districts had a negative variance value, (2)Sijunjung regency revenue growth was lower than Dahrmasraya, (3)the effectiveness ratio of total revenue of Sijunjung district was higher than Dharmasraya district, (4)the ratio of the effectiveness of the original revenue of the Sijunjung district is higher than the Dharmasraya district, (5)the realization of operating expenditure to the total realization of the Sijunjung district expenditure is higher than the Dharmasraya, (6)the ratio of capital expenditure realization to the realization of the total Sijunjung district expenditure is lower than Dharmasraya, (7)Sijunjung district expenditure efficiency ratio is lower than Dharmasraya, (8)Sijunjung district financial independence ratio is higher than Dharmasraya, (9)Sijunjung district financial dependency ratio is lower than Dharmasraya district and (10)Sijunjung district financial independence ratio is higher than Dharmasraya.